Analisis Kepuasan Pengguna terhadap Sistem Operasional Lima Jaya Melalui Metode Cabanillas - Saraswati, Sartika; Astiti, Sarah (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Lima Jaya Savings and Loans Cooperative (KSP) is engaged in savings and loans business and has thirteen branches in Central Java Province, Lima Jaya KSP innovates by creating an information system called the OP Lima Jaya system to support employee operational activities. The implementation of the OP Lima jaya system has several technical obstacles such as limited access time, server down when system access is done at the same time, input data is overloaded due to a full database, and new users experience difficulties in using the system. This study was conducted with the aim of conducting an analysis of the OP Lima jaya system so that the factors that affect system user satisfaction can be known using the Cabanillas method having five measurement scales including Accessibility, Ease of Use, Trust, Usability, and User Satisfaction using statistical calculations SEM-PLS / SmartPLS using outer model and inner model measurement models.The results in this study consist of validity tests, reliability of getting valid results on each variable. In the hypothesis test, five hypotheses obtained significant results on H2, H5, H6, H7, H10, while on H1, H3, H4, H8, H9 obtained insignificant results because the p-value had a value of <0.05/=0.05.